Study of some Impact Of Enterococcus faecium As Probiotic On Chick 2- Newcastle Disease Antibody And White blood cells: Emad J.khamas and Amjad H.Elaywe - khamas, Emad J. (The Iraqi Journal of Veterinary Medicine, 2007)
To investigate the impact of Enterococcus faecium as a probiotic in theperformance of layer male chicks and some aspects of immunity, Newcastle diseaseantibodies and the blood picture, this bacteria was given in the feed of layer malechicks with a dose rate of 1.5 g\kg of feed, each kg of feed contained (5×1011CFU)along the experiment which last 57 days. 150 male chicks were divided into fivegroups, the 1st group was given the probiotic in the feed, the 2nd group was given theprobiotic and was exposed to bad ventilation and high temperature as a stress, thethird group was given the probiotic and chlortetracycline in the feed, the fourth groupwas given the probiotic and then infected with E. coli on day 21 of the experiment,and the fifth group was given the feed only without the probiotic as a control group.Results showed that giving Enterococcus faecium in the feed had insignificant effecton Newcastle antibodies tested on day 37 of the experiment, and the effect wassignificant on day 57. Also, the differential count of the white blood cells wasincreased while the heterophile\lymphocyte ratio was decreased in the groups whichwere given probiotic, compared with the control.